2012
DOI: 10.1016/j.procbio.2012.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic modification of 2,6-dimethoxyphenol for the synthesis of dimers with high antioxidant capacity

Abstract: Abstract2,6-Dimethoxyphenol is a phenolic compound that is extensively used for the measurement of laccase activity, but is often not exploited for its potential as an antioxidant compound. Since laccase can be used to modify phenolic antioxidants as a way of improving their activities, the present study investigated the laccase-mediated oxidation of 2,6-dimethoxyphenol in biphasic or homogenous aqueous-organic media for the production of compounds with higher antioxidant capacity than the starting substrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 48 publications
1
17
1
3
Order By: Relevance
“…Furthermore, the coupling of 2,6-dimethoxyphenol was also investigated at the aforementioned conditions. The reaction led selectively to the formation of dimer 8 in 80% yield, contrary to a previously reported study, where four demethylated products were also observed employing laccase from Trametes pubescens [49]. During the oxidative coupling of 2,6-dimethoxyphenol, Q1 is produced by recombination of two para radical species.…”
Section: Substrate Screeningcontrasting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the coupling of 2,6-dimethoxyphenol was also investigated at the aforementioned conditions. The reaction led selectively to the formation of dimer 8 in 80% yield, contrary to a previously reported study, where four demethylated products were also observed employing laccase from Trametes pubescens [49]. During the oxidative coupling of 2,6-dimethoxyphenol, Q1 is produced by recombination of two para radical species.…”
Section: Substrate Screeningcontrasting
confidence: 83%
“…Further reaction of this compound with laccase can lead either to its re-aromatization into compound 8 or to the formation of the very stable quinone 7 (Scheme 3) which show different molar masses. In the literature, depending on the study, the formation of 8 or 7 was reported [49], [50]. In this experiment, mass spectroscopy resulted in a molar mass of 304 g/mol attributed to the quinone 7.…”
Section: Substrate Screeningmentioning
confidence: 65%
“…To date, there are no reports describing syringol O -demethylation or, more broadly, even its catabolism by microbes. Rather, the best-studied biological reaction of syringol is its 4–4 dimerization to form cerulignone (3033).…”
mentioning
confidence: 99%
“…Os compostos fenólicos naturais com atividade antioxidante estão presentes em baixas concentrações em relação a um substrato oxidável e recebem atenção pela capacidade de retardar ou inibir a oxidação desse substrato (ADELAKUN et al, 2012b). Muitos dos compostos fenólicos naturais são sensíveis à temperatura, pH e à luz devido à presença de duplas ligações alternadas (NEMADZIVA et.…”
Section: Introductionunclassified
“…O apelo ambiental é o grande impulsionador desta abordagem, pois possibilita a modificação dos substratos sem o uso de substâncias químicas e em condições brandas, com baixo impacto ambiental. Os radicais formados pela ação dos biocatalisadores resultam, geralmente, na formação de novas moléculas com propriedades biológicas de interesse (ADELAKUN et al, 2012b;MUNIZ-MOURO et al, 2017).…”
Section: Introductionunclassified